Using Wikis in an English for Specific Academic Purposes (ESAP) context: University Students’ Perceptions and Reflections - Papadima-Sophocleous, Salomi; Yerou, Christina (My University, 2013)
This study explores students' perceptions regarding the use of wikis in their learning of English for Specific Academic Purposes (ESAP). First year university students of the department of Commerce, Finance and Shipping were given a questionnaire prior to and after their ESAP course. Students worked with wikis during the entire semester and recorded their reflections concerning the wiki integration and its perceived effect on their language learning. The results show that the wiki experience was a positive one overall.